GAMBARAN GANGGUAN KADAR NATRIUM SERUM PADA PASIEN STROKE DI RSUP PROF. DR. R.D. KANDOU MANADO - Kembuan, Mieke A. H. N. (Jurnal Biomedik : JBM, 2013)
Abstract: World-wide, stroke is a main public health problem. It is one of the leading causes of chronic disability and death. Both hyponatremia and hypernatremia have a negative influence on the outcome of strokes. Hyponatremia is associated with increased mortality and complication rate, meanwhile hypernatremia is often found in the treatment of cerebral oedema in strokes. There are scarce data about natrium level disorders in acute strokes, especially from developing countries. This study aimed to describe the incidence of natrium disorders among acute stroke patients, and the difference of means of natrium based on the severity of the stroke and on GCS at admission. This was a hospital-based cross-sectional study. Samples consisted of 82 patients that met the inclusion criteria. The data of natrium levels were obtained from the hospital medical records. The results showed that the incidence of natrium disorders among acute stroke victims was 30%. The mean natrium level was 138.01 Meq/L (95% CI, 135.83-140.20). The incidence of hyponatremia was 28% while hypernatremia was 2%. There was no difference of mean-natrium-levels based on the severity of strokes (P > 0.05) and of GCS (P > 0.05). Conclusion: The incidence of natrium disorders among acute stroke patients was high but there was no difference between mean natrium levels based on the severity of strokes and of GCS. Keywords: natrium, natrium level disorders, acute stroke. Â  Â  Abstrak: Stroke termasuk dalam masalah kesehatan utama di masyarakat dan merupakan penyebab utama kecacatan kronik dengan angka mortalitas tertinggi ke-2 di seluruh dunia. Baik hiponatremia maupun hipernatremia memberikan pengaruh negatif terhadap keluaran stroke. Hiponatremia meningkatkan angka kematian dan komplikasi, sedangkan hipernatremia sering terdeteksi bersamaan dengan penanganan edema serebral pada stroke. Data mengenai insidens gangguan kadar natrium pada stroke akut masih sangat kurang, terutama dari negara-negara berkembang. Penelitian ini bertujuan untuk mendapatkan insidens gangguan kadar natrium pada pasien stroke akut dan deskripsi perbedaan rerata kadar natrium pada berbagai derajat defisit neurologi dan GCS saat masuk rumah sakit. Penelitian ini bersifat potong lintang berbasis rumah sakit dengan jumlah sampel sebanyak 82 dan kriteri inklusi tertentu. Hasil penelitian memperlihatkan angka insidens gangguan kadar natrium pada stroke akut sebesar 30%. Rerata kadar natrium 138.01 Meq/L (95% CI, 135,83-140,20). Hiponatremia didapatkan pada 28% kasus sedangkan hipernatremia pada 2% kasus stroke akut. Tidak terdapat perbedaan bermakna antara rerata kadar natrium berdasarkan beratnya stroke dan GCS (P > 0,05). Simpulan: Insidens gangguan kadar natrium pada stroke akut tinggi. Tidak terdapat perbedaan bermakna antara rerata kadar natrium berdasarkan beratnya stroke dan GCS. Kata kunci: natrium, gangguan kadar natrium, stroke akut.